Industrial Revolution 4.0's Information Technology's Impact on the Growth of MSMEs in the Manufacturing Industries Sector - Ahmad Gunawan; Rini Kartika Hudiono (Pandawan Sejahtera Indonesia, 2023)
The expansion of Micro, Small, and Medium Businesses (MSMEs) can have an impact on Indonesia's economic growth (MSMEs). Because MSME players lack the capacity to adapt new technology, new technology in the industrial era 4.0 is one of the barriers to the development of MSMEs in Indonesia.Due to the inability of MSME players to adapt new technologies, Indonesia. Sales information systems, social networking, and Google My Business are a few examples of technologies that MSME & SMEs may use to their advantage. These technologies can aid in sales, marketing, and customer communication. The aim of this study was to ascertain the extent to which MSMEs in Banyumas Regency employ information technology, including information systems, social media, and Google My Business. information technology's impact on Banyumas Regency MSMEs' success. The research approach employed is The findings demonstrated the significant growth of MSMEs using technologies like Tokopedia, Instagram, and Google Maps. Use of technologies like Tokopedia, Instagram, and Google Maps is expanding quickly. A combination of increased asset turnover and customer communication is made simpler. According to these findings, there is a high correlation between the two factors, suggesting that the usage of industrial information technology (IIT) 4.0 might influence MSMEs' development. in order to say that there is a substantial correlation between the two variables.